ANALYSIS OF MEASLES SURVEILLANCE BASED ON SYSTEM APPROACH IN BANGKALAN HEALTH OFFICE - Fitria, Annisa; Syahrul, Fariani; Damayanti, Siska Dwi (HEARTY, 2024)
Background: Measles and rubella are one of the VPDs that very contagious with the average number of secondary cases caused by people who transmit the disease in susceptible populations estimated at 12-18 cases. Measles and rubella are the highest number of VPD cases in Bangkalan, however the findings of secondary cases of measles and rubella did not reach the minimum estimated number. Purpose: To analyze the measles and rubella surveillance system at the Bangkalan Regency Health Office using a systems approach (input, process, output). Method: The design of this study was a descriptive qualitative study conducted at the Bangkalan Regency Health Office in January until February 2024. There were 4 respondents to this study including 1 Head of the Surveillance and Immunization Division, 1 Person in Charge of the Surveillance Program, and 2 staff members of the Surveillance and Immunization Division. Data was collected by conducting in-depth interviews and secondary document studies. Results: Active surveillance from the Bangkalan Health Office to visit hospitals is still carried out once a month and is not routine. Not all hospitals are routinely targeted by active surveillance. Conclusion: This study shows that the detection of suspected measles cases by active surveillance in Bangkalan Regency is not optimal.